Are plants sentient?. (28th September 2017) - Calvo, Paco; Sahi, Vaidurya Pratap; Trewavas, Anthony
Abstract: Feelings in humans are mental states representing groups of physiological functions that usually have defined behavioural purposes. Feelings, being evolutionarily ancient, are thought to be coordinated in the brain stem of animals. One function of the brain is to prioritise between competing mental states and, thus, groups of physiological functions and in turn behaviour. Plants use groups of coordinated physiological activities to deal with defined environmental situations but currently have no known mental state to prioritise any order of response. Plants do have a nervous system based on action potentials transmitted along phloem conduits but which in addition, through anastomoses and other cross‐links, forms a complex network. The emergent potential for this excitable network to form a mental state is unknown, but it might be used to distinguish between different and even contradictory signals to the individual plant and thus determine a priority of response. This plant nervous system stretches throughout the whole plant providing the potential for assessment in all parts and commensurate with its self‐organising, phenotypically plastic behaviour. Plasticity may, in turn, depend heavily on the instructive capabilities of local bioelectric fields enabling both a degree of behavioural independence but influenced by the condition of the whole plant. Abstract : The phloem is the pathway for plant electrical communication. In this opinion article, we report that this system is cross‐linked, is thus nervous‐like, and explore several potential properties. Prioritisation between different signals may be one of this system's emergent capabilities. Animals prioritise their signal responses using sentience. We suggest some future investigations to clarify functioning and the potential involvement of bioelectric fields in both learning and memory.